ON THE DEVELOPMENT OF INFORMATION-ANALYTICAL CENTRE FOR POPULATION RADIATION PROTECTION OF ROSPOTREBNADZOR - L. V. Repin; A. M. Biblin; A. A. Bratilova; M. S. Nikolaevich (Радиационная гигиена)
Article is devoted to the development of Information-Analytical Centre for Population Radiation Protection of Rospotrebnadzor.